Chitosan as a basis of stimuli-sensitive systems: a systematic review (review) - V. S. Pyzhov; V. S. Ganykin; D. M. Vlasova; Ya. D. Petukhova; A. I. Khodenok; E. O. Bakhrushina (Разработка и регистрация лекарственных средств)
Introduction. The actual trend of modern drug development is the creation of stimuli-sensitive systems capable of solution-gel phase transition in the human body under the influence of various physiological factors (ionic composition of the medium, temperature, pH, etc.). One of the most promising stimuli-responsive natural polymers is a deacetylated derivative of the main structural component of crustacean shells, chitin – chitosan. This polymer has proven high compatibility with animal tissues, biodegradability and its own antimicrobial action, which allows its non-limited use in pharmaceutical compositions. It is also worth noting the high prevalence of chitosan in nature, which makes it an easily obtainable raw material for the creation of new dosage forms and, in particular, for import substitution of foreign polymers in Russian pharmaceutical technology.Text. The aim of the survey presented here is to systematise information and studies on chitosan, its production, physical and chemical properties and factors on which the above depend, and, most importantly, pharmaceutical compositions based on the studied polymer and its modifications and stimuli, due to which the phase transition occurs in delivery systems involving this deacetylated natural polysaccharide. Chitosan, an amino polysaccharide composed of β-(1 → 4)-linked D-glucosamine and N-acetyl-D-glucosamine residues, has been known in the pharmaceutical industry since the middle of the XX century. Over the years of research, its biocompatibility, mucoadhesiveness and gel-forming abilities in aqueous solutions at pH in the range up to 6–7 have been proven. The most investigated chitosan-based compositions included various low molecular weight auxiliary components to achieve in situ transition of its aqueous solutions under physiological conditions, but many crosslinking components resulted either in the formation of stationary hydrogels or possessed toxic properties. One of the most promising and investigated combinations to the present day appears to be the combination of chitosan with beta-glycerophosphate.Another interesting strategy for providing chitosan with stimulus-sensitive properties is to modify the free amino groups of the polymer chain with other high molecular weight compounds by crosslinking them through imine or amide bonds (as in methoxypolyethylene glycol-chitosan, for example), which are able to hydrolyse in the body's environment. In such way, it is possible to increase the solubility of chitosan and to achieve pH- and/or thermosensitivity in the polymers studied.Conclusion. In the write-up of this review, the most important aspects of chitosan production and modification have been highlighted, and ways to impart pH- or thermosensitive properties to chitosan through different strategies have been demonstrated and their advantages and disadvantages have been shown. Significantly, no work was found to prove the presence of stimulus-sensitive properties in individual chitosan solutions.